Student Representation in Solving Story Problems Using Polya Steps - Mohammad Archi Maulyda; Sukoriyanto Sukoriyanto; Vivi Rachmatul Hidayati; Muhammad Erfan; Umar Umar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2020)
The purpose of this descriptive qualitative study is to look at the representation of students in solving problems about stories. Subjects were selected based on the results of the pretest questions and short interviews conducted on 28 students in 1 class. Of the 28 students who were the subjects of the study, 2 students were chosen representing 2 categories of answers that appeared in 1 class. Each category, namely the category of students who answered correctly and students who answered incorrectly, were randomly assigned to one student for further analysis. The research location was Malang Saladin Middle School. Subjects will be given test questions and will be interviewed to gather information regarding the results of their work. The results of this study indicate that there are still students who have difficulty in solving mathematical problems in the form of story problems. This research also shows that repressance plays an important role in the success of students in solving story problems.